FORGEdb: a tool for identifying candidate functional variants and uncovering target genes and mechanisms for complex diseases - Charles E. Breeze; Eric Haugen; María Gutierrez-Arcelus; Xiaozheng Yao; Andrew Teschendorff; Stephan Beck; Ian Dunham; John Stamatoyannopoulos; Nora Franceschini; Mitchell J. Machiela; Sonja I. Berndt (Genome Biology, 2024)
Abstract The majority of disease-associated variants identified through genome-wide association studies are located outside of protein-coding regions. Prioritizing candidate regulatory variants and gene targets to identify potential biological mechanisms for further functional experiments can be challenging. To address this challenge, we developed FORGEdb ( https://forgedb.cancer.gov/ ; https://forge2.altiusinstitute.org/files/forgedb.html ; and https://doi.org/10.5281/zenodo.10067458 ), a standalone and web-based tool that integrates multiple datasets, delivering information on associated regulatory elements, transcription factor binding sites, and target genes for over 37 million variants. FORGEdb scores provide researchers with a quantitative assessment of the relative importance of each variant for targeted functional experiments.